2014
DOI: 10.1080/13546783.2013.875942
|View full text |Cite
|
Sign up to set email alerts
|

Belief bias is stronger when reasoning is more difficult

Abstract: Three studies examine the influence of varying the difficulty of reasoning on the extent of belief bias, while minimising the possibility that the manipulation would influence the way participants approach the task. Specifically, reasoning difficulty was manipulated by making variations in problem content, while maintaining all other aspects of the problems constant. In Study 1, 191 participants were presented with consistent and conflict problems varying in two levels of difficulty. The results showed a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
2
4
0
4
Order By: Relevance
“…In this situation, the ability of people to monitor the conflict increases (as shown by the increased RT and decreased FOR) as does the ability to overcome it, which would then result in a decrease of the effect of conclusion belief. Such an analysis is indeed consistent with recent results relating the extent of belief bias to reasoning difficulty (Brisson et al, 2014).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In this situation, the ability of people to monitor the conflict increases (as shown by the increased RT and decreased FOR) as does the ability to overcome it, which would then result in a decrease of the effect of conclusion belief. Such an analysis is indeed consistent with recent results relating the extent of belief bias to reasoning difficulty (Brisson et al, 2014).…”
Section: Resultssupporting
confidence: 91%
“…It should be noted that many studies that examine the effects of belief attempt to combine different forms of reasoning, including valid and invalid forms, in order to look at the so-called belief by validity interaction (e.g., Evans et al, 1983). However, a recent study has shown that factors such as the complexity of reasoning influence the extent of belief-bias independently of validity (Brisson, de Chantal, Lortie Forgues & Markovits, 2014). Thus, we decided to conduct separate studies examining interactions between reasoning strategy and individual forms of syllogistic reasoning.…”
mentioning
confidence: 99%
“…Therefore, one can clearly be evaluated as skilled on MPP in a CFA content but fails to be in CMA. This claim is supported by the results of many studies carried out by our team members (Brisson et al, 2014). This reasoning content categorization not only provides a framework for classifying reasoning skills, but also a way to organized reasoning learning activities (or items).…”
Section: Fig 1 Logic-muse Expert Componentsupporting
confidence: 70%
“…Also, the smaller-than-expected effect size may point to the relative relevance of the presently found domainspecific belief bias effects: The domain-specific belief bias effects were less strong than the generally found belief bias effects. Alternatively, it could be that this less strong effect was a result of our effort to create easier syllogisms: Indeed, the effect of belief bias has been found to decrease with easier syllogisms (Brisson, de Chantal, Forgues, & Markovits, 2014).…”
Section: Discussionmentioning
confidence: 99%